Modelling with Spectral Methods for Engineering Application - Magdalena PALACZ (Communications of International Proceedings, 2021)
Advanced methods of detection and identification of structural damages guide the efforts of scientific research groups to improve their diagnostic methods based, among other things, on the phenomenon of mechanical wave propagation. Damage detection methods utilising the phenomenon of mechanical wave propagation are highly effective. Many different numerical approaches are applied to model this phenomenon, but due to their versatile character, spectral methods, are most frequently used. In this paper, an overview of latest research works in this field is presented to show the differences and effectiveness of the two most popular spectral methods used for modelling the wave propagation problem in terms of the detection of damage. As an important aspect of Technical System Management is considered also Innovation & Technology in Product Development it would be interesting to consider the numerical reliability of the most popular numerical modelling methods. Therefore, it has been decided to present this very brief insight into the subject.
Keywords: Numerical Modelling; Spectral Methods.